Corporate Social Responsibility dalam Pemberdayaan Masyarakat Desa Wisata Baruga Collaboration Center di Malili Kabupaten Luwu Timur - Asrivana Yusuf Mangin; Arimurti Kriswibowo (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
In the implementation of CSR PT. Vale is empowering the community, one of which is by building the Baruga Collaboration Center tourism village. This research was conducted with the aim of knowing, describing and analyzing Corporate Social Responsibility (CSR) in Community Empowerment of the Baruga Collaboration Center Tourism Village in Malili, East Luwu Regency. The research method used in this research is descriptive qualitative. The sampling technique that used is purposive sampling and snowball sampling. From the results of the research obtained, it shows that: (1) Awareness in CSR community empowerment in BCC tourism villages has been carried out by soliciting proposals through socialization so BCC tourism villages is exists and all stakeholders know the mission and goals of BCC tourism villages. (2) The organization has not been optimal, it is shown from the management in the BCC tourism village by Bumdesma which is stuck which causes activities and empowerment in the BCC tourism village stop. (3) The regeneration carried out in the BCC tourism village has not fulfilled the overall sub-focus regeneration. This shows that it is necessary to conduct trainings that are more in line with the needs of the community related to conditions in BCC tourism village by providing direct training to the community. (4) Support obtained from PT. Vale that is the provider of the CSR itself, but from the Baruga Village government itself, it is still a few. (5) It has not fulfilled the system management sub-focus because in increasing its capacity, the BCC tourism village community has not yet reached the BCC tourism village destination because there is still community dependence (not yet independent).